P49 Efficacy and safety of mepolizumab in severe eosinophilic asthma: a real life study. (December 2018) - Mitchell, V; Howles, K; Mansur, AH
Abstract : Background: Mepolizumab has been recommended by NICE in 2017 for patients with severe eosinophilic asthma. Aim: To investigate the efficacy and tolerability of mepolizumab treatment in severe eosinophilic asthma in a tertiary centre Methods: All patients treated with mepolizumab from June 2017 to May 2018 in our centre and completed at least 6 months on treatment were included in this study. We compared baseline clinical outcomes (that included adjusted baseline exacerbation rate to 6 months) and the 6 months on treatment using standard statistics. Results: In total, 39 patients were included in the analyses (29 female 74%, mean age=49 years (range 19–75). Comparing baseline to 6 months on treatment, there was significant reduction in the mean rescue oral corticosteroid (OCS) courses from 2.7±0.89 to 1.18±1.37 (p<0.0001), and significant reduction in the median maintenance prednisolone dose from 10 mg/day (IQR 0–20) to 5 mg (IQR 0–10) (p=0.028). The asthma control questionnaire7 (ACQ7) improved from a mean of 3.19±1.17 to 2.63±1.42 (p=0.0002), alongside marked reduction in the peripheral blood eosinophils from a mean of 790±0.62 cells/µl to 86±0.07 (p<0.0001). However, there was no significant change in the mean forced expiratory volume in 1 s (FEV1) 1.86±0.79L to 1.88±0.69L (p=0.8117), or fraction exhaled nitric oxide (FeNO) which was marginally reduced from 58 ppb ±46.15 to 45±38.51 (p=0.0621). Majority of patients tolerated the treatment well. Eight patients (21%) experienced side effects (5 had worsening eczema, 1 light headiness, 1 headache, and 1 tachycardia). Six (15.4%) stopped treatment prematurely (3 pregnancies and 3 due to side effects). Conclusion: This preliminary data showed significant reduction in OCS requiring exacerbations and mean maintenance prednisolone treatment following 6 months of mepolizumab treatment in patients with severe eosinophilic asthma. The treatment was generally well tolerated. The 12 months outcomes data will be available for presentation in the conference.